Earnings instability and tenure - Lorenzo Cappellari; Marco Leonardi (Institute for the Study of Labor (IZA), 2006)
This paper develops a tractable empirical approach to estimate the effect of on-the-job tenure on the permanent and the transitory variance of earnings. The model is also used to evaluate earnings instability associated with fixed-term contracts (short-tenure contracts) in Italy. Our results indicate that each year of tenure on the job reduces earnings instability on average by 15%. Workers on a fixed-term contract on average have an earnings instability 10% higher than workers on a permanent contract. Workers who spend their entire working life on fixed-term contracts can expect an earnings instability twice as high.
urn:nbn:de:101:1-20080429133
Keywords: 330